Role of community on Destination Development: A case Study of Holy Tree Kanzemane and Holy Waterfall Chumi Gyaste, Tawang, Arunachal Pradesh (Journal of Pharmaceutical Negative Results, 2023)
Community based tourism is the involvement of local community to uplift tourism in their neighborhood, as well as a a way of sustainable tourism that allows travellers to closely connect to local communities.In the proposed study, focus has been given on how local communities can be involved  in destination development focusing on religious tourism. It attempts to assess the participation level of government and local community in application of religious tourism as an adaptive strategy of community based tourism. Selected areas for the study are two places with religious value located in the Tawang district of Arunachal Pradesh. Both places have diverse potential to attract tourists. The study was done mostly through primary data collected from tourists who have visited the places. The study aimed at identification of areas besides religious tourism which could be developed  in the study areas.